Technology for Learning and Knowledge Strategies in Virtual Education: A Case Study of Higher Education - López-Aguilar, Diego (2023)
This research is oriented to the application of Information and Communication Technologies based on Learning and Knowledge Technologies, for the development of virtual environments that improve concentration, creativity, and student interest in virtual or face-to-face classes. The objective pursued by the research is to relate ICT and TAC in the development of personal learning environments in students of higher education. The methodology used is experimental, exploratory through a quantitative approach. The technique used was the survey, using two instruments; a structured questionnaire focused on web 3.0 tools used as a pre-test, made up of 24 questions, later the previously validated instrument was applied as a post-test based on the Technology Acceptance Model (TAM) made up of 15 questions in which measures the acceptance of digital resources. The instruments were validated using the Cronbach's Alpha statistic, having high-reliability values. The population used for this research was 49 students: obtaining as a result the acceptance of the Moodle educational platform. Recognizing that ICT and TAC are fundamental in the educational field since they demonstrate an innovative educational strategy that fosters interaction with free web 3.0 tools available on the Internet, where students prefer to work with TAC tools on gamification platforms due to their ease of use demonstrating greater interest in collaborative work, optimizing time and resources.